Peningkatan Performa Termal Dengan Menggunakan Vortex Generators Didalam Saluran Persegi Panjang - Effendi, Yafid; Rosyidin, Ali; Setiawan, Bambang (Jurnal Teknik, 2024)
Vortex generators (VGs) are an effective method for improving the thermal performance of heat exchangers. This study aims to optimize the heat transfer rate by employing VGs, where airflow passes over a heated cylinder within a rectangular duct equipped with vortex generators. An experimental approach was conducted to investigate the enhancement of heat transfer using concave delta winglet (CDW) and delta winglet (DW) VGs, compared to the baseline condition without VGs. The experiments involved variations in the angle of attack (β) at 10°, one VG pairs, and the arrangement types (in-line and staggered). The cylinder was heated with a constant power of 35 W, reaching a surface temperature of 38 °C, and airflow velocities ranged from 0.4 to 2 m/s. Temperature measurements were taken at the inlet, outlet, and cylinder surface using thermocouples. The research results indicate a significant enhancement in the convective heat transfer coefficient when using vortex generators (VGs). Among the various configurations tested, the staggered concave delta winglet pair (CDW) arrangement demonstrated the highest values in terms of convective heat transfer coefficient, friction factor ratio, and performance evaluation criterion (PEC), followed by the in-line CDW, staggered delta winglet pair (DW), and in-line DW configurations. The highest convective heat transfer coefficient was observed in the staggered CDW configuration, reaching 16.02%. The friction factor ratio (f/fo) for this configuration was 108.67%. The highest PEC value, 26.34%, was achieved with a single staggered CDW pair at a Reynolds number of Re = 11,000.